1992
DOI: 10.1128/iai.60.3.1008-1017.1992
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of salivary agglutinin-mediated adherence and aggregation of mutans streptococci by use of monoclonal antibodies against the major surface adhesin P1

Abstract: The ability to adhere to salivary agglutinin-coated hydroxyapatite beads and to aggregate in the presence of fluid-phase salivary agglutinin was tested by using 25 isolates of mutans streptococci representing eight serotypes. Both adherence and aggregation activity correlated with expression of the Mr-185,000 cell surface antigen P1 on Streptococcus mutans serotype c, e, and f strains. In addition, it was shown that the P1 molecule itself served as the adhesin of S. mutans serotype c, since adherence was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 70 publications
8
111
0
5
Order By: Relevance
“…1.0 ± 0.00 ns 11.9 ± 0.32*** 9.8 ± 2.53*** 4.0 ± 2.21*** -Four units at risk §Twelve fissures at risk Twenty units at risk ns, not significant; *** P < 0.001 SpaP into the medium instead of expressing the protein on their surface do not adhere well to saliva-coated hydroxyapatite (14). Streptococcus mutans UA159 and OMZ64 were not included in that study and their mode of SpaP expression remains unknown.…”
Section: Discussionsupporting
confidence: 92%
“…1.0 ± 0.00 ns 11.9 ± 0.32*** 9.8 ± 2.53*** 4.0 ± 2.21*** -Four units at risk §Twelve fissures at risk Twenty units at risk ns, not significant; *** P < 0.001 SpaP into the medium instead of expressing the protein on their surface do not adhere well to saliva-coated hydroxyapatite (14). Streptococcus mutans UA159 and OMZ64 were not included in that study and their mode of SpaP expression remains unknown.…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to the observation by Chatenay-Rivauday et al (1998) that the V region alone from S. mutans AgI/IIf adhered to monocytes. The V region also appears to carry primary epitopes for adherence to salivary glycoproteins (Brady et al, 1992;Kelly et al, 1995). There may be sequences within the NA region that bind integrin directly, or the NA region may be required for functional conformation of the V region.…”
Section: Discussionmentioning
confidence: 99%
“…The present study focuses on streptococci. Numerous studies have demonstrated that along with the lactobacilli, the streptococci can produce the quantities of lactic acid necessary to demineralize teeth (22). It is therefore of interest to study the mechanisms by which these particularly cariogenic bacteria are dealt with by host defences.…”
Section: Discussionmentioning
confidence: 99%